Exploring Students’ Experiences of Hybrid Listening Class - Nurul Afiyattena; Siti Hanna Sumedi; Isma Ristiyana (Journal of English Development, 2024)
This study aims to explore students' engagement experiences in hybrid listening class. Three experiences of engagement were dig by the researcher those were behavioral, emotional, and cognitive engagement. The qualitative research method with a narrative inquiry was used in this study. The participants were 8 students from the fifth semester of a university in Indonesia. The data were collected through interviews and student reflections. The thematic analysis was used to analyze the data. The finding revealed that experiences related to behavioral engagement: noticing the lecturer’s explanation, and class participation (asking questions, learning practice) were more active in offline sessions than in online sessions. In addition, students showed their dominant engagement during offline sessions in cognitive activities like learning planning, efforts, strategies, challenges, and student achievements. Meanwhile, for emotional experience, students were enjoyed and happy with both sessions (online/offline), one of the reasons is its flexibility, especially for the listening material which allowed students to slowly grasp concepts and ensure full comprehension in both sessions. In essence, although students have an interest in hybrid learning, students still have a preference and a high tendency for offline sessions.